Régimen general de los contratos asociativos mercantiles, con particular referencia a su duración temporal - Zegarra Mulánovich, Alvaro (Revista de Derecho, 2019)
This article discusses the handful of positive rules that the Civil Code and the General Law on Corporations devote to the regulation of the category of contracts called “associative contracts”. It then addresses an issue not explicitly provided for or settled in any of these rules, namely the need to subject all “associative contracts” to a maximum duration limit.